2007
DOI: 10.1523/jneurosci.2858-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Neonatal Ventromedial Hypothalamus Transcriptome Reveals Novel Markers with Spatially Distinct Patterning

Abstract: The ventromedial hypothalamus (VMH) is a distinct morphological nucleus involved in feeding, fear, thermoregulation, and sexual activity. It is essentially unknown how VMH circuits underlying these innate responses develop, in part because the VMH remains poorly defined at a cellular and molecular level. Specifically, there is a paucity of cell-type-specific genetic markers with which to identify neuronal subgroups and manipulate development and signaling in vivo. Using gene profiling, we now identify ϳ200 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 61 publications
5
151
0
Order By: Relevance
“…We investigated the metabolic role of PACAP, a pleiotropic neuropeptide, which was recently identified by microarray as a "VMN-enriched" gene (Segal et al, 2005;Kurrasch et al, 2007).…”
Section: Identifying Pacap As a Vmn Phenotypic Markermentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the metabolic role of PACAP, a pleiotropic neuropeptide, which was recently identified by microarray as a "VMN-enriched" gene (Segal et al, 2005;Kurrasch et al, 2007).…”
Section: Identifying Pacap As a Vmn Phenotypic Markermentioning
confidence: 99%
“…Like many hypothalamic neurons, at least some of the effects of SF-1 cells in the VMN are mediated by glutamate (Tong et al, 2007), although neuropeptidergic classifications remain elusive. Microarray studies have identified a number of VMN-enriched genes, including the neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP) (Segal et al, 2005;Kurrasch et al, 2007), which has been implicated in many central functions (for review, see Vaudry et al, 2000). The pleiotropic nature of this peptide has made it difficult to study in terms of energy balance; however, in this study, we have shown by in vivo pharmacological and histological methods that the VMN PACAP population partially mediates responses to leptin, and that PACAP exerts robust effects on both appetite and energy expenditure in mice.…”
Section: Introductionmentioning
confidence: 99%
“…2C), novel molecular markers of VMH in the newborn mouse were identified (Kurrasch et al, 2007). Many of these neuroendocrine markers exhibit distinct regional expression patterns in the newly formed hypothalamus.…”
Section: Patterning Of Developing Thalamus and Hypothalamus By Secretmentioning
confidence: 99%
“…Because nPE1 and nPE2 are functional analogs, it is conceivable that these sequences recruit a common, yet unidentified TF able to transactivate Pomc in the hypothalamus. Pomc expression starts in the ventral lining of the developing mouse hypothalamus at embryonic day 10.5 (E10.5) (15)(16)(17), a precise spatiotemporal domain in which multiple HDTFs determine the early patterning of the mouse ventral hypothalamus (19,20). Therefore, we considered of interest to investigate whether the terminal differentiation of melanocortin-expressing neurons is regulated by a HDTF.…”
mentioning
confidence: 99%